Isolation of Potential Nitrogen-Fixing Phylloplane Bacteria and in Vitro Detection of Their Ability to Inhibit the Growth of Colletotrichum: Isolation of Potential Nitrogen-Fixing Phylloplane Bacteria and in Vitro Detection of Their Ability to Inhibit the Growth of Colletotrichum - Widiantini, Fitri; Syahnur, Fitika; Hidayat, Yusup; Yulia, Endah (Jurnal Fitopatologi Indonesia, 2024)
Isolation of Potential Nitrogen-Fixing Phylloplane Bacteria and in Vitro Detection of Their Ability to Inhibit the Growth of Colletotrichum Anthracnose is one of the significant diseases in chili plants caused by Colletotrichum spp., with potential yield losses of up to 100%. The negative impact of fungicide use forces the search for biocontrol agents as part of environmentally friendly disease management. One of the sources where these biocontrol agents can be found is in the phyllosphere. This experiment aimed to obtain antagonistic bacteria from the phyllosphere of healthy chili plants that have the potential to be developed as biocontrol agents and potentially increase the nutrition uptake through nitrogen-fixation. Healthy chili plants were obtained from red chili plantations in Cijambu Village and Nanggerang Village, Sumedang Regency, West Java. Isolation using Nitrogen-free media and screening for antagonistic activity resulted in the isolation of eight bacterial strains, namely strains CJB1, CJB2, CJB3, CJB4, CJB5, NGR1, NGR2, and NGR3. The antagonistic tests on these eight bacterial strains were then conducted against various Colletotrichum spp. strains from different chili cultivation centers in Garut, Lembang, Sumedang, and Jatinangor. The testing was carried out using a dual-culture method followed by the examination of volatile compound activity using the double compartment method. The results showed that phyllosphere bacteria NGR1, CJB1, and CJB5 consistently demonstrated abilities to inhibit the growth of four Colletotrichum spp. strains, both directly through antagonistic tests and based on the volatile anticendawan compound activity produced by these bacterial strains. Malformations in the mycelium of Colletotrichum spp. were also detected when the pathogen was directly exposed to phyllosphere bacteria or their volatile compounds. This experiment indicates that phyllosphere bacteria that potentially capable of fixing nitrogen also have the potential to be developed as biocontrol agents for Colletotrichum spp.